Vulnerability of public buildings subjected to earthquake by finite element modelling - Adnan, Azlan; Suradi, Suhana; Selvanayagam, P. N.; Darus, Zamri (2006)
Tremors in Peninsular Malaysia and East Malaysia due to Sumatra and Philippine earthquakes have been reported several times. Engineers are concerned of the seismic vulnerability of public buildings due to lack of earthquake consideration in Malaysia’s building design procedure. This study addresses the vulnerability of public buildings in Malaysia subjected to earthquakes from Sumatra and Philippines. A case study has been conducted on low rise to medium rise reinforced concrete buildings, which are mostly categorized as moment resisting frames. The buildings are analyzed using Finite Element Modeling (FEM) under different types of analyses including Free Vibration Analysis (FVA), and Time History Analysis (THA) considering low to medium earthquake intensities. The study indicates that more than 50% of the buildings produced dynamic amplification factors of slightly more than one indicating not much of a dynamic response to the buildings. The performances of the structure are shown by the yield point at beam-column connections where the internal forces at beam elements exceed the design capacity of the beams. In the non-linear analysis, the largest damage index is still under the intermediate level where no structural damage is indicated, but some non-structural damage are expected.